Improving quality of care among patients hospitalised with schizophrenia: a nationwide initiative. Issue 1 (June 2015) - Jørgensen, Mette; Mainz, Jan; Svendsen, Marie Louise; Nordentoft, Merete; Voldsgaard, Inge; Baandrup, Lone; Bartels, Paul; Johnsen, Søren Paaske
Abstract : Background: The effectiveness of systematic quality improvement initiatives in psychiatric care remains unclear. Aims: To examine whether quality of care has changed following implementation of a systematic monitoring programme of hospital performance measures. Method: In a nationwide population-based cohort study, we identified 14 228 patients admitted to psychiatric departments between 2004 and 2011 from The Danish Schizophrenia Registry. The registry systematically monitors the adherence to guideline recommended processes of care. Results: The overall proportion of all relevant recommended processes of care increased from 64 to 76% between 2004 and 2011. The adherence to individual processes of care increased over time, including assessment of psychopathology using a diagnostic interview (relative risk (RR): 2.01, 95% CI: 1.51–2.68), contact with relatives (RR: 1.44, 95% CI: 1.27–1.62), psychoeducation (RR: 1.33, 95% CI: 1.19–1.48), psychiatric aftercare (RR: 1.06, 95% CI: 1.01–1.11) and suicide risk assessment (RR: 1.31, 95% CI: 1.21–1.42). Conclusions: Quality of care improved from 2004 to 2011 among patients hospitalised with schizophrenia in Denmark.